Features of Ground Flashes before and after the Massive Earthquake Observed from Kathmandu, Nepal - Adhikari, Pitri Bhakta (Journal of Nepal Physical Society, 2017)
Lightning electric field signatures pertinent to the subtropical thunderstorms occuring over the rugged terrain have been measured and recorded at a hilly station Kathmandu, Nepal. In the present work signatures of the ground flashes have been selected from all the records before and after the massive earthquake and were analyzed. It is the first time that such signatures were analyzed and presented. Two hundred and eight flashes (208) of the totals of six hundred and forty–five (645) flashes were selected from about eight thunderstorm days before and after the massive earthquake and analyzed. Majority of the positive ground flashes were found to be single stroke ones whereas the average number of strokes per flash is found to be 1.13 with a maximum value of 4, after the massive earthquake. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 11-22